Respiratory syncytial virus seasonality in three epidemiological zones of Kenya. Issue 2 (10th December 2020) - Rose, Erica Billig; Nyawanda, Bryan O.; Munywoki, Patrick K.; Murunga, Nickson; Bigogo, Godfrey M.; Otieno, Nancy A.; Onyango, Clayton; Chaves, Sandra S.; Verani, Jennifer R.; Emukule, Gideon O.; Widdowson, Marc‐Alain; Nokes, D. James; et al.
Abstract: Understanding respiratory syncytial virus (RSV) circulation patterns is necessary to guide the timing of limited‐duration interventions such as vaccines. We describe RSV circulation over multiple seasons in three distinct counties of Kenya during 2006‐2018. Kilifi and Siaya counties each had consistent but distinct RSV seasonality, lasting on average 18‐22 weeks. Based on data from available years, RSV did not have a clear pattern of circulation in Nairobi. This information can help guide the timing of vaccines and immunoprophylaxis products that are under development.